2021
DOI: 10.3748/wjg.v27.i22.3037
|View full text |Cite
|
Sign up to set email alerts
|

Role of imaging in evaluating the response after neoadjuvant treatment for pancreatic ductal adenocarcinoma

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is a highly aggressive malignancy. Despite the development of multimodality treatments, including surgical resection, radiotherapy, and chemotherapy, the long-term prognosis of patients with PDAC remains poor. Recently, the introduction of neoadjuvant treatment (NAT) has made more patients amenable to surgery, increasing the possibility of R0 resection, treatment of occult micro-metastasis, and prolongation of overall survival. Imaging plays a vital role in tumor respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 64 publications
0
23
0
Order By: Relevance
“…[ 62 , 63 ] The concept behind radiomics is that medical images contain much more information than is visible to the eyes of radiologists, which is called “hidden” information. [ 64 ] Radiomics combined artificial intelligence (AI) algorithms, particularly deep learning, has demonstrated remarkable progress in pancreatic image-recognition tasks including tumor classification, [ 65 , 66 , 67 ] grade, [ 68 , 69 , 70 ] survival, [ 71 , 72 ] treatment respond prediction, [ 73 , 74 , 75 , 76 ] lymphatic metastasis, [ 77 , 78 , 79 ] tumor microenvironment, [ 80 , 81 , 82 ] and so on. In the future, the diagnosis of pancreatic diseases will enter an era of precision and individuation.…”
Section: Discussionmentioning
confidence: 99%
“…[ 62 , 63 ] The concept behind radiomics is that medical images contain much more information than is visible to the eyes of radiologists, which is called “hidden” information. [ 64 ] Radiomics combined artificial intelligence (AI) algorithms, particularly deep learning, has demonstrated remarkable progress in pancreatic image-recognition tasks including tumor classification, [ 65 , 66 , 67 ] grade, [ 68 , 69 , 70 ] survival, [ 71 , 72 ] treatment respond prediction, [ 73 , 74 , 75 , 76 ] lymphatic metastasis, [ 77 , 78 , 79 ] tumor microenvironment, [ 80 , 81 , 82 ] and so on. In the future, the diagnosis of pancreatic diseases will enter an era of precision and individuation.…”
Section: Discussionmentioning
confidence: 99%
“…Endoscopic ultrasound (EUS) is highly sensitive in detecting small tumors that are often missed by other imaging modalities, and it also provides an opportunity to collect samples (fine needle aspirates) for cytological or biomarker analysis to facilitate the most conclusive diagnosis 177 . Metabolic PET imaging, which relies on the differential uptake of 18 F-labeled fluoro-deoxy glucose (FDG) by rapidly growing tumor cells, enables whole-body imaging to detect both primary tumors and metastasis and is used alone or in combination with CT and MRI for evaluating the response to therapy in PDAC patients 178 , 179 . The principles, utility, and current status of various imaging modalities are elegantly reviewed in several recent articles 178 , 180 - 182 .…”
Section: Nanocarrier-based Delivery Of Therapeutic Imaging and Theran...mentioning
confidence: 99%
“…10 Research has shown that patients with borderline resectable PDAC have a resection rate of 60%-68% after NAT. [11][12][13] However, evaluating the effect of NAT is very important; at present, serological markers and computed tomography (CT) are the main evaluation methods used in clinics. [14][15][16] Although the response evaluation criteria for solid tumor (RECIST) evaluation system has been used to analyze the efficacy of clinical trials, 17,18 after NAT with CT many PDAC patients have no significant changes in tumor volume 16 ; however, changes in tumor tissue composition and density are present.…”
mentioning
confidence: 99%
“…Through NAT, borderline resectable PDAC can be treated with radical surgery, which helps to improve the surgical resection rate and prognosis of PDAC 10 . Research has shown that patients with borderline resectable PDAC have a resection rate of 60%–68% after NAT 11–13 …”
mentioning
confidence: 99%